2011
DOI: 10.1186/1532-429x-13-78
|View full text |Cite
|
Sign up to set email alerts
|

3D Echo systematically underestimates right ventricular volumes compared to cardiovascular magnetic resonance in adult congenital heart disease patients with moderate or severe RV dilatation

Abstract: BackgroundThree dimensional echo is a relatively new technique which may offer a rapid alternative for the examination of the right heart. However its role in patients with non-standard ventricular size or anatomy is unclear. This study compared volumetric measurements of the right ventricle in 25 patients with adult congenital heart disease using both cardiovascular magnetic resonance (CMR) and three dimensional echocardiography.MethodsPatients were grouped by diagnosis into those expected to have normal or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 29 publications
4
52
1
Order By: Relevance
“…Other annular measurements are also made directly onto the short-axis view not taking into account the true nonplanar configuration 3D echocardiography can underestimate measurements compared with other imaging modalities, such as CT 26 and magnetic resonance imaging. 27 This may be due in part to suboptimal lateral resolution in the coronal plane of 3D echocardiography, which reduces the ability to discriminate the blood/ tissue interface. 26 Nonetheless, this study demonstrated good agreement between MA dimensions derived by 3D-TEE and CT.…”
Section: Discussionmentioning
confidence: 99%
“…Other annular measurements are also made directly onto the short-axis view not taking into account the true nonplanar configuration 3D echocardiography can underestimate measurements compared with other imaging modalities, such as CT 26 and magnetic resonance imaging. 27 This may be due in part to suboptimal lateral resolution in the coronal plane of 3D echocardiography, which reduces the ability to discriminate the blood/ tissue interface. 26 Nonetheless, this study demonstrated good agreement between MA dimensions derived by 3D-TEE and CT.…”
Section: Discussionmentioning
confidence: 99%
“…To what extent the use of 3D imaging has improved the accuracy of echocardiographic examination of RV size and function is less clear. Ongoing concerns regarding 30% to 40% underestimation of RV volumes by 3D echocardiography 13 are difficult to reconcile with a recent meta-analysis that reported a small (but still significant) underestimation of CMR-derived RV volumes by 3D echocardiographic methods in multiple recent human studies.…”
Section: Accuracy and Validitymentioning
confidence: 95%
“…In a comparison study of the RV volume measurement of using 3DE and MRI imaging, Crean et al (2011) acquired RV from a modified four-chamber imaging view to maximize the visualization of RV. The volume reconstruction was performed from 2D multiplanar view for semi-automatic intracardial boundary detection with manual correction.…”
Section: Rv Volume Measurement Methodsmentioning
confidence: 99%
“…This process is a routine step of the ventricle assessment procedures, where often, in clinical reports, many parameters can be measured in these two stages to help in diagnosing and decision making Barcaro et al (2008). However, the process of detecting the ED and ES still a challenge for diagnosis because it was mostly done manually by tracking the cine loop during the clinical procedure, as in Niemann et al (2007) or by optical tracking of the change of ventricle dimensions through watching the individual image faces of the ventricle during the cardiac cycle, as in (Aune et al, 2009;Crean et al, 2011).…”
Section: End-diastolic and End-systolic Detectionmentioning
confidence: 99%